KAUSALITAS ANTARA PEMBENTUKAN MODAL TETAP DAN PERTUMBUHAN EKONOMI DI EMPAT NEGARA ASEAN (PHILIPINA, MALAYSIA, SINGAPURA DAN INDONESIA) - Rahmatullah Rizieq (Jurnal Bisnis dan Ekonomi, 2006)
The debate between De Long and Summerrs (1991) and Blomstrom, Lipsey and Zejan (1996) who reported conflicting results on the relationship between fixed capital formation and economic growth raised doubts onwhether changes in a country’s capital formation shares in GDP have an influence on its futer growth rate. This paper addresses the issue again by examining the causal patterns between the share of fixed investment in GDP and the growth rate of per capita real GDP on an individual country basis, using time series on each of four countries of ASEAN. The empirical results suggest that the causal relationship between these variables may vary significantly across that countries. Most importantly, no consistent evidence is found that causality is running in only one direction. Rather, causality between fixed investment and growth seems to have a country-specific nature and may run in either direction.Keywords : Fixed capital, economic growth